The European "Training of Trainers Network" TTnet and its German section "TTnet Germany" - Groß, Herold [Verfasser]; Grollmann, Philipp [Verfasser] (My University, 2007)
"The quality of general and vocational education systems depends to a large degree on the quality of teaching staff. Europe needs a pool of competent, motivated and committed VET staff who are capable of mastering challenges of ever-increasing complexity. This article presents the European Network TTNet: the "Training of Trainers Network". TTNet is a network set up and moderated by the European Centre for the Development of Vocational Training, Cedefop, and aimed at teaching and training staff in vocational education. Taking the structure and activities of this network as a starting point, the article presents key functions of its European and national-level networks and some perspectives of their work." (BIBB)
Keywords: P 3.2.1 Ausbilder; I 1.4 Berufsbildungsprojekte/Entwicklungsprojekte; S 3.5.5.1 CEDEFOP; I 2.2 Europa; Ausbilder; Bildungspersonal; Qualifizierung; Netzwerk; Europäische Union